Odpowiedzi

2010-04-12T14:17:00+02:00
A)
12x-13=2x+26
12x-2x=26+13
10x=39
x=3,9


b)
x-4+(2x-1)=x-2
x-4+2x-1=x-2
x+2x-x=-2+4+1
2x=3
x=1,5


c)
1-(x-3)=3(2x+1)
1-x+3=6x+3
-x-6x=3-1-3
-7x=-1
x=¹/₇
2010-04-12T14:17:18+02:00
A) 12x-13=2x+26
10x=39
x=3,9

b) x-4+(2x-1)=x-2
x-4+2x-1=x-2
3x-5=x-2
2x=3
x=3/2
x=1,5
c) 1-(x-3)=3(2x+1)
1-x+3=6x+3
-x+4=6x+3
-7x=-1
x=1/7
2010-04-12T14:31:29+02:00
A) 12x-13=2x+26
12x - 2x =26 + 13
10x = 39
x = 39 : 10
x = 3,9
spr.
12 * 3,9 - 13 = 2 *3,9 + 26
46,8 - 13 = 7,8 + 26
33,8 = 33,8
L = P

b) x-4+(2x-1)=x-2
x - 4 + 2x - 1 = x - 2
x + 2x - x = (-2) +4 + 1
2x = 3
x = 3 : 2
x = 1,5

Spr.
1,5 - 4 + 2 * 1,5 - 1 = 1,5 - 2
1,5 - 4 + 3 - 1 = (-0,5)
(-0,5) = (-0,5)
L = P

c) 1-(x-3)=3(2x+1)
1 - x + 3 = 6x + 3
-x - 6x = 3 - 1 - 3
-7x = (-1)
x = (-1) : (-7)
X = 1/7
Spr.
1 – (1/7 - 3) = 3 (2 * 1/7 + 1)
1 - 1/7 + 3 = 3 (2/7 + 1)
3 i 6/7 = 6/7 + 3
3 i 6/7 = 3 i 6/7
L = P